The Efficacy of Sulodexide in the Prevention of Postthrombotic Syndrome. (September 2014) - Luzzi, Roberta; Belcaro, Gianni; Dugall, Mark; Hu, Shu; Arpaia, Guido; Ledda, Andrea; Ippolito, Edmondo; Corsi, Marcello; Ricci, Andrea; Cotellese, Roberto; Agus, Giovanni; Errichi, Bruno M.; et al.
Aim: The aim of this open, observational registry was to evaluate the effects of antithrombotic treatment on the development of postthrombotic syndrome (PTS): the effects of "standard management" (SM; according to International Union of Angiology guidelines) were compared to SM in association with sulodexide or aspirin. Methods: Postthrombotic syndrome occurrence was observed in 3 nonparallel groups after deep venous thrombosis (DVT); the registry started after the end of the anticoagulation period. The target was to observe the occurrence of PTS in 5 years. Three possible options were suggested to the patients, and the patients and their caregivers defined the type of management. A group of 167 patients was involved in the SM with reevaluation every 6 months; the sulodexide group included 124 patients and the aspirin group included 48 patients. Results: The 3 groups were clinically similar and comparable for age and sex distribution. Of the 167 patients in the SM group, 154 patients completed 60 months of follow-up. The percentage of patients with PTS in the SM group ranged from 14.9% (1 year after the end of anticoagulation) to 19.5% (60 months). In the nonparallel group using sulodexide (124 comparable patients at inclusion; 115 at 60 months), the percentage of PTS was variable from 8.8% (1 year after anticoagulants) to 12.17% at 60 months. These percentages are significantly lower than those observed with SM. In the nonparallel aspirin group (48 patients at inclusion and 34 at 54 months), there was a PTS incidence of 23.5% at 54 months (vs 12.17% in the sulodexide group and 18.23% in the SM group). The incidence of PTS was significantly higher in comparison with the other 2 groups. The incidence of PTS was lower in the sulodexide group in comparison with the 2 other groups. Conclusions: Sulodexide administration after DVT appears to be effective in preventing PTS in association with recommended management and a number of recurrent DVTs. Modalities of treatment, dosages, and timing of administration should be explored in more comprehensive and complete studies.